GENRE ANALYSIS ON READING PASSAGES GRADE VII ENGLISH TEXTBOOKS - Ardini Nur Sukma (Universitas PGRI Semarang, 2010)
Abstract Referring to the latest curriculum, School-Based Curriculum, every English textbook should provide genres based on the level of literacy of each grade. On this paper, I analyzed English textbooks published by Erlangga ?óÔé¼ÔÇ£ English on Sky (EOS), and by Pakar Raya – Let?óÔé¼Ôäós Talk. This paper focuses on how are the reading passages of the textbooks compatible with ?óÔé¼?ôStandard Isi?óÔé¼?Ø?. Coinciding with the statement of the problems, the objectives of this paper are to describe the generic structures of the texts, the types of text, linguistic features, social purposes, and then their compatibility to ?óÔé¼?ôStandar Isi?óÔé¼?Ø. There are some crucial problems found such; the types of text provided in EOS were Descriptive (80%) and Procedure (20%), whereas in Let?óÔé¼Ôäós Talk were Descriptive (57.2%) and Procedure (42.8%). Looking at the percentage of both text types, I found a crucial problem in EOS on some texts and in applying simple continuous tense in descriptive text. To sum up the result, I conclude that Let?óÔé¼Ôäós Talk is more compatible than EOS. Keywords: Genre, text, social purpose, generic structure, linguistic features, School-Based Curriculum (KTSP), English textbook, communicative competence, ?óÔé¼?ôStandar Isi?óÔé¼?Ø.